Outcomes of Corneal Patch Grafts in a Tertiary Eye Hospital in Nepal - Pandey, Manish; Luitel, Pragya; Karn, Rajiv Ranjan; Dev, Mahesh Kumar (Nepalese Journal of Ophthalmology, 2024)
Introduction: Corneal patch graft is a surgery performed as a temporary or definitive treatment of corneal perforations or thinning and descemetoceles. Objective: To determine the outcomes of corneal patch grafts, in corneal thinning or perforations, in terms of anatomical and functional success. Methodology: This retrospective study included a total of 28 eyes of 27 patients who underwent corneal patch grafts for the treatment of corneal perforations or thinning >2 mm. The preoperative indications for performing corneal patch grafts, the size and site of corneal perforation or thinning and preoperative best corrected visual acuity (VA) were recorded. The post-operative results were evaluated in terms of structural integrity (anatomical success), using a slit lamp biomicroscopy and visual outcome (functional success) by testing best corrected VA, defined as best corrected VA ≥6/60, at final follow-up. Result: The mean age (mean ± SD) of patients was 35.75 ± 21.40 years, and 71.42% were males. Corneal thinning or perforations due to microbial keratitis was the most common indication for corneal patch grafts (46.42%), followed by immune-mediated peripheral ulcerative keratitis (21.42%). Peripheral corneal perforation or thinning was the most common location (71.42%). The mean follow-up was 8.43 ± 7.92 months. While anatomical success was seen in 24 of 28 eyes (85.71%), functional success was attained in 17 out of 28 eyes (60.71%). Conclusion: Corneal patch grafts showed a high success in terms of both maintaining anatomical integrity and functional success. Corneal patch grafts could be used as a good therapeutic modality for the treatment of corneal thinning and perforations.